Avifaunal study of Majalgaon Reservoir and their tributaries, District Beed, Marathwada region of Maharashtra, India - Pawar, R. T.; Pathan, T.S.; Bhosale, Y.M. (International Journal of Scientific Research in Biological Sciences, 2019)
An avifaunal survey was conducted at Majalgaon Reservoir for two years, starting from July 2016 to June 2018. The study reveals a rich avian diversity a total of 84 species of birds belonging to 15 orders and 30 families were identified. As the water of the wetland is clear, rich in dissolved oxygen and supports variety of aquatic weeds and fishes, it has been found to be suitable for birds and attracts many migratory birds like large egert, purple heron, white bellied heron, asian open bill stork, greater flamingo, white naked stork etc. Continuous monitoring on the avifaunal diversity was suggested to evaluate the ecological status of the habitats and birds. It can be considered as an efficient tool to the environmentalists, policy makers in order to conserve such species, because, the role of birds in an ecosystem cannot be ignored.